Reconstructing the ecological restoration pattern from the perspective of ecosystem health assessment in a typical black soil region of Northeast China - Feng, Duo; Zhou, Panpan; Wang, Dongyan; Shi, Pu (Frontiers in Environmental Science, 2023)
Assessments on the spatial pattern of ecological restoration potential provide insights into the current status of ecosystem health, facilitate the identification of hotspots of ecosystem degradation, and further serves as a link that bridges regional ecological planning with specific restoration efforts. The goal of this study was to reconstruct the ecological restoration pattern, through establishing an ecosystem health assessment model encompassing four elements of vigor, organization, resilience and service of an ecosystem. Siping City, a typical black soil region located in central Jilin Province of Northeast China, was selected as the study area, and ecological protection and restoration units were identified based on temporal changes in ecosystem health levels from 2000 to 2020. Getis-Ord Gi* analysis was adopted to classify the restoration zones and depict the spatial pattern of ecological restoration. From 2000 to 2020, the ecosystem health index of Siping City generally increased from 0.49 to 0.51 due to increases in forestland area and precipitation, but a fraction of suburban areas also experienced decreases. Four different restoration zones were delineated, including the windbreak and sand-fixing zone in the western part, the black soil protection and reclamation zone in the middle part, the Daheishan ecological shelter zone in the central and eastern part, and the water restoration zone in the eastern part, which account for 28.12%, 37.05%, 16.53% and 18.29% of the total area. The protection units covered an area of 1189.83 km2 and the restoration units covered an area of 2009.83 km2, which could be further classified into 10 types and accounted for 31.24% of the total area. It was suggested that the restoration methods applied to different units should be tailored towards specific restoration objectives. This proposed methodological framework serves as a basis for reconstructing ecological restoration in the black soil region, and a reference for making restoration plans elsewhere.